2012
DOI: 10.1002/stem.1206
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Blood‐Derived Aldehyde Dehydrogenase‐Expressing Progenitor Cells Promote Recovery from Acute Ischemic Injury

Abstract: Umbilical cord blood (UCB) represents a readily available source of hematopoietic and endothelial precursors at early ontogeny. Understanding the proangiogenic functions of these somatic progenitor subtypes after transplantation is integral to the development of improved cell-based therapies to treat ischemic diseases. We used fluorescence-activated cell sorting to purify a rare (<0.5%) population of UCB cells with high aldehyde dehydrogenase (ALDH hi ) activity, a conserved stem/progenitor cell function. ALDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 53 publications
2
71
0
Order By: Relevance
“…As reported by Hess et al, ALDH high HSPCs from TCB demonstrated reliable NOD/SCID repopulating function [39]. Furthermore, UCB ALDH high cells are considered to be proangiogenic progenitors that integrate into ischemic tissue and promote vascular regeneration [40]. Isolated HSPCs according to their enhanced ALDH activity in PCB demonstrated a HSPC phenotype and higher in-vitro clonogenic potential than in TCB.…”
Section: Discussionmentioning
confidence: 73%
“…As reported by Hess et al, ALDH high HSPCs from TCB demonstrated reliable NOD/SCID repopulating function [39]. Furthermore, UCB ALDH high cells are considered to be proangiogenic progenitors that integrate into ischemic tissue and promote vascular regeneration [40]. Isolated HSPCs according to their enhanced ALDH activity in PCB demonstrated a HSPC phenotype and higher in-vitro clonogenic potential than in TCB.…”
Section: Discussionmentioning
confidence: 73%
“…Recently, cell-based therapies have attracted a high level of attention as a novel treatment for neonatal encephalopathy [6] . Studies have shown that human umbilical cord blood (hUCB) cell therapies provide beneficial effects in a number of diseases because hUCB cells contain several types of stem cells, such as those expressing the CD34 cell-surface marker (hematopoietic stem/endothelial progenitor cells) [7,8] . In preclinical studies using neonatal models with brain injuries, >10 studies have proven the therapeutic efficacy of hUCB cell treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental approaches have been undertaken to enhance regeneration or restore lost functions after stroke with exogenously injected or transplanted human-induced pluripotent stem cells [10], umbilical cord blood-derived aldehyde dehydrogenase-expressing progenitor cells [11], and endothelial progenitor cells from umbilical cord [12]. Recent studies predicted that intensifying neuronal differentiation and survival around the ischemic area can improve the clinical outcome.…”
Section: Introductionmentioning
confidence: 99%